PERSEPSI SISWA TENTANG MANAJEMEN PESERTA DIDIK DI SMK TRI DHARMA KOSGORO 2 PADANG - Dini Oktaria (Universitas Negeri Padang, 2013)
The goal of this research are to get information about indicating management of student. The population is one hundred and ten students. And the sample is ninety, that taken by krejcie table. The instrument of this research is question Likert scale models that had tested for validiy and reliability. Data analyzed using mean score. The result of this research are indicating management of student in Tri Dharma Kosgoro 2 Vocational School Padang is Good Enough. Keywords : management of student